RECURRENCE OF PULMONARY TUBERCULOSIS ASSOCIATED WITH COMORBIDITIES - CURRENT INTERDISCIPLINARY PROBLEM - Elena TUDOR; Constantin IAVORSCHI; Albina BRUMARU; Stela KULCITSKAIA; Lidia RIVNAC; Valentina BOLOTNICOVA; Andrei CORLOTEANU; Ecaterina AXENTII; Anna MOSCOVCIUC; Svetlana MATVYEYEVA; Olga SHEVCHENKO; Irina PIRLOG; et al. (Academy of Sciences of Moldova, 2024)
Introduction. The recurrence of pulmonary tuberculosis remains a significant public health problem in many countries of the world, despite the remarkable progress in the treatment and rehabilitation of patients with new cases of tuberculosis. It is demonstrated that the high incidence of recurrence of pulmonary tuberculosis is conditioned by the influence of some factors combination. Currently, the comorbidities, which impose the risk of disease recurrence directly or indirectly, are of a major importance. Thus, it is important to study the clinical and epidemiological characteristics of pulmonary tuberculosis recurrence associated with the comorbidities. Materials and methods. There were studied 715 patients with pulmonary tuberculosis recurrence, including 503 patients with comorbidities, as well as statistical reporting data for the Right Bank region of the Dniester River and ATU (Autonomous Territorial Unit) of Gagauzia, Republic of Moldova during 2019-2021. Results. The obtained results demonstrate that in phthisiopulmonology the presence of comorbidities constitutes a significant and important medico-social problem. In the structure of relapses associated with comorbidities, it was noted the predominance of extensive infiltrative processes, high frequency of cases with destruction in the lung tissue and bacillary cases. The need to review and improve the general antituberculosis measures accepted both in the work of phthisiopneumologists and primary care specialists is argued in order to improve the prognosis of TB treatment associated with comorbidities. Conclusion. The recurrence of pulmonary tuberculosis associated with comorbidities requires an integrated multidisciplinary approach.